Analisis Kinerja Pegawai Badan Pusat Statistik di Kabupaten Aceh Singkil - Sarina Sarina; Keumala Fadhiela ND (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2022)
The performance of employees in an agency determines the effectiveness of the service process obtained by the community, as well as employees at the Central Statistics Agency (BPS) Kabupaten Aceh Singkil  as the basis for presenting data under the auspices of the state. The purpose of this study was to determine and analyze the performance of employees at the Central Bureau of Statistics of Aceh Singkil Regency. The approach used in this research is quantitative research. The data collection method uses a questionnaire. The number of samples in this study were 21 respondents. The results showed that the three independent variables used in this study had an influence on employee performance, as it was found that the value of sig. > 0.05, i.e. 0.007 <0.05, so it can be concluded that simultaneously the quality of work, quantity of work and work performance have a significant effect on the work achievement of BPS employees in Aceh Singkil Regency. Furthermore, through the three independent variables above, the dependent variable in this study is answered, namely employee performance. Based on the results of multiple linear regression analysis showing maximum results with a number of 98.00 to 100.00, this figure can be translated that so far the performance of the Central Statistics Agency (BPS Kabupaten Aceh Singkil) is classified as good, both in terms of quality, quantity and work performance.Keywords: Analysis, Employee Performance, Central Bureau of Statistics Aceh Singkil Regency.